Derivação de um skewness da velocidade vertical turbulenta a partir de um modelo LES - Maldaner, Silvana (2010)
The planetary boundary layer (PBL) is a physical system presenting a variety of complex states characterized by the turbulence phenomenon. An understanding of the turbulence patterns and its structural details is of fundamental importance in large and small meteorological scales and atmospheric dispersion. From the numerical point of view, the PBL turbulence has been investigated employing LES models. In LES, only the energy-containing eddies of the degrees of freedom of the turbulent field are explicitly resolved and the effect of the smaller, more isotropic eddies, needs to be parameterized. Modeling these residual turbulent motions, which are also termed subfilter-scale motions, is in large part a phenomenological procedure based on heuristic arguments. These movements are called subfiltro or subgrade and the description of its effects is a major problem in the formulation models of large eddy simulation. Therefore, the derivation of subfilter viscosities expressed in terms of a cutoff wave number is a fundamental procedure in LES methodology. The purpose of the present study is to derive a new turbulent subfilter viscosity based on the energy at cutoff from the Taylor statistical diffusion theory. As an additional purpose, this new viscosity is used in a LES model to obtain a new profile of the vertical velocity skewness in the convective boundary layer (CBL). A comparison between the results of the skewness generated by the LES simulation with the observed skewness values in surface shows that the calculated numerically values are consistent with those observed. Vertical profiles of the simulated skewness by the LES is employed in a Lagrangian stochastic diffusion model to reproduce the contaminants concentrations measured during the Prairie Grass experiment. This new profile simulated from the LES can be used in diffusion models to reproduce the observed contaminants concentrations.